Establishment of a High Canine Rabies Burden in Haiti through the Implementation of a Novel Surveillance Program [corrected]. - Ryan M Wallace; Hannah Reses; Richard Franka; Pierre Dilius; Natael Fenelon; Lillian Orciari; Melissa Etheart; Apollon Destine; Kelly Crowdis; Jesse D Blanton; Calvin Francisco; Fleurinord Ludder; et al. (Public Library of Science (PLoS), 2015)
The Republic of Haiti is one of only several countries in the Western Hemisphere in which canine rabies is still endemic. Estimation methods have predicted that 130 human deaths occur per year, yet existing surveillance mechanisms have detected few of these rabies cases. Likewise, canine rabies surveillance capacity has had only limited capacity, detecting only two rabid dogs per year, on average. In 2013, Haiti initiated a community-based animal rabies surveillance program comprised of two components: active community bite investigation and passive animal rabies investigation. From January 2013 -December 2014, 778 rabies suspect animals were reported for investigation. Rabies was laboratory-confirmed in 70 animals (9%) and an additional 36 cases were identified based on clinical diagnosis (5%), representing an 18-fold increase in reporting of rabid animals compared to the three years before the program was implemented. Dogs were the most frequent rabid animal (90%). Testing and observation ruled out rabies in 61% of animals investigated. A total of 639 bite victims were reported to the program and an additional 364 bite victims who had not sought medical care were identified during the course of investigations. Only 31% of people with likely rabies exposures had initiated rabies post-exposure prophylaxis prior to the investigation. Rabies is a neglected disease in-part due to a lack of surveillance and understanding about the burden. The surveillance methods employed by this program established a much higher burden of canine rabies in Haiti than previously recognized. The active, community-based bite investigations identified numerous additional rabies exposures and bite victims were referred for appropriate medical care, averting potential human rabies deaths. The use of community-based rabies surveillance programs such as HARSP should be considered in canine rabies endemic countries.